Shroom: A Cultural History of the Magic Mushroom - Sveta Yamin‐Pasternak (Ethnobiology Letters, 2010)
Review of Shroom: A Cultural History of the Magic Mushroom. Andy Letcher. 2007. Ecco HarperCollins, New York. Pp. 384. $14.99 (paperback). ISBN 9780060828295.